World Markets for Organic Fresh Citrus and Juice - James J. Ferguson (EDIS)
Given the lack of official foreign trade data on organic sales, Pascal Liu, Commodities Specialist, The Food and Agriculture Organization, has interviewed trade and industry figures and reviewed available sources to develop a perspective on the current market situation and medium-term prospects for fresh organic citrus and juices. Information presented here is based on his May, 2003 paper on World markets for Organic Citrus and Citrus Juices, available at http://www.fao.org/es/ESC/common/ecg/28303_en_CitrusorganicEN.pdf. This fact sheet summarizes the above FAO publication as a general aid to Florida organic citrus growers and others in assessing their export potential for international markets. This document is HS978, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2004.